Synthesis and Modifications of Nylons Having Bromine and Azide Functionalty - Ozkan, Melek; Akat, Hakan (Asian Journal of Chemistry, 2012)
In this study, new aliphatic polyamides which containing bromine were synthesized by using 2,3-dibromosuccinyl chlorides and different long chain diamines. Polymerization was performed via interfacial polymerization. The polymers were characterized by FTIR, 1H NMR, TG and viscosity measurement. According to the thermo-analytical, the thermal degradations of polyamides were increased by introduction of bromine moieties into polymer backbone. These aliphatic polyamides have inherent viscosities in the range of 0.19-0.65 dL/g in H2SO4 at 25 ºC. Solubility of these polymers also discussed. It is observed that polyamides with bromine increased flame-retardation and also these polymers may find use in a variety of click chemistry strategy because of azide functionality.